2016
DOI: 10.1007/s12520-016-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Timber economy in the Roman Age: charcoal data from the key site of Herculaneum (Naples, Italy)

Abstract: The city of Herculaneum (Naples, southern Italy), buried by the volcanic eruption of Mount Somma-Vesuvius in 79 ad, is a key site for understanding the timber economy during the Roman period. In this paper, the results of charcoal analysis of different building element types are presented. Beams, joists, poles, planks and door and window frames were investigated allowing us a view of which timber the Romans preferred for building in this area. We also fit the taxonomic results into the reconstruction of the an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…78 Tacitus, 1925), but also in timber plantations. Recent studies have shown that it was utilised in the construction of luxurious Roman villas, such as the Villa of Poppaea at Oplontis near Naples and the houses of Herculaneum (Moser et al, 2013;Moser et al, 2016). In Roman times, cypress wood was largely used in shipbuilding and other structures in long contact with water (Allevato et al, 2009;Colaianni et al, 2011;Sadori et al, 2015).…”
Section: Cypress Wood Use In Ancient Architecturementioning
confidence: 99%
“…78 Tacitus, 1925), but also in timber plantations. Recent studies have shown that it was utilised in the construction of luxurious Roman villas, such as the Villa of Poppaea at Oplontis near Naples and the houses of Herculaneum (Moser et al, 2013;Moser et al, 2016). In Roman times, cypress wood was largely used in shipbuilding and other structures in long contact with water (Allevato et al, 2009;Colaianni et al, 2011;Sadori et al, 2015).…”
Section: Cypress Wood Use In Ancient Architecturementioning
confidence: 99%
“…The pollen grains embedded in the dental calculus, as a consequence of possible accidental aspiration due to breathing, may testify the existence of the relative plant species in the past environments [19, 36]. Indeed, Juglans regia , Castanea sativa Mill., and Olea europaea L. were already diffused in the Mediterranean landscape and highly appreciated by the Romans for their timber and fruits [48, 49]. However, pollen could also be remained entrapped in tartar after ingestion processes.…”
Section: Resultsmentioning
confidence: 99%
“…; b) P. abies (Norway spruce) ranges from about 800 to 2200 m a.s.l.. Since roman times and through the Middle Age, the woods of these two species have always been economically important both as structural woods and for their use in domestic and industrial products [33][34][35]. These considerations were consistent with the radiocarbon dating of the lock, around the XVI-XVIII centuries and with SEM analyses where the image of samples 2 highlighted the typical vessel structures of hardwood [1].…”
Section: Discussionmentioning
confidence: 99%